Effect of Implementing the Google Classroom Based on Learning Motivation, Interest in Learning and Student Learning Outcomes in Craft and Entrepreneurship Subjects - Ponimin; Riki Mukhaiyar; Yeka Hendriyani; Hasan Maksum (JTP - Jurnal Teknologi Pendidikan, 2024)
Advancements in modern technology provide teachers with opportunities to develop their skills in using media and teaching materials. This shift helps transform the instructional paradigms used in school learning processes, making education more modern and high-quality. Therefore, teachers need to be proficient in using information technology to enhance classroom learning, especially in subjects like crafts and entrepreneurship. This study is a quantiative research that focuses on examining the impact of Google Classroom on students' learning motivation, interest, and outcomes. The research was conducted at SMK Negeri 1 Tualang, Tualang District, Siak Regency, with a sample size of 95 eleventh-grade students. The data collected from this study were deemed valid and reliable, particularly concerning the influence of Google Classroom on learning motivation. The research findings were obtained through the use of questionnaires, with 33 respondents, providing data on the Google Classroom variable with a maximum score of 40. This indicates that there is a significant difference between the learning outcomes of students who were taught using the Online Google Classroom Learning Method and those taught using the conventional learning model in the subject of Crafts and Entrepreneurship for the 10th-grade students of SMK Negeri 1 Tualang in the Odd Semester of the Academic Year 2023/2024.